(untitled) (Journal of Medicine, 2017)
Mitochondrial disease, once thought to be a rare clinical entity, is now recognized as an important cause of a wide range of neurologic, muscle, cardiac and endocrine disorders. Kearns Sayre syndrome is a rare mitochondrial disease, involving deletion of mitochondrial DNA. This syndrome ischaracterized by progressive external ophthalmoplegia (PEO), retinitis pigmentosa and an onset before the age of 20 years. First case was reported in 1958. We are reporting a case with chronic progressive external ophthalmoplegia, bilateral partial ptosis with onset at 10 years of age. He also had features of myopathy and neuropathy without any fatigable weakness. Our diagnosis is mostly based on clinical background and by exclusion of other common disorders, as definitive diagnostic investigation genetic testing due to unavailability so was not done. J MEDICINE Jan 2018; 19 (1) : 66-69